Controversies of radiotherapy in human epidermal growth factor receptor (HER)-2 positive breast cancer patients - Kolarova, Iveta; Melichar, Bohuslav; Vanasek, Jaroslav; Ryska, Ales; Horackova, Katerina; Petera, Jiri; Vosmik, Milan; Sirak, Igor; Dolezel, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
Tumor biology plays a crucial role in the systemic treatment, specifically in HER2-positive tumors. Distinct biological behavior of breast cancer subtypes is associated with different rates of locoregional recurrence (LRR). HER2- positive breast cancer patients treated with surgery in combination with radiation, without trastuzumab have poor outcome, including high LRR. The efficacy of radiotherapy in HER-2-positive breast cancer appears to be associated with the expression of estrogen receptors. In patients with HER-2-positive breast cancer, studies conducted before the introduction of trastuzumab indicated higher benefit of adjuvant radiation in patients with hormone receptor-positive tumors compared to patients with tumors not expressing hormone receptors. The introduction of agents targeting HER-2 has transformed the management of these patients, resulting in improved outcomes. The data of clinical studies show that the administration of trastuzumab as part of a multimodality approach (with radiation based on standard guidelines) results in improved outcomes, including lower locoregional recurrence. The risk of cardiac toxicity associated with radiation to the heart and administration of potential cardiotoxic trastuzumab is not clear. In patients treated concomitantly with regional lymph node irradiation and anti-HER-2 agents after prior anthracycline-based chemotherapy minimizing the dose to the myocardium, e.g. respiratory gating or proton beam radiotherapy, have been suggested.
Keywords: receptor erbB-2; nádory prsu; locoregional recurrence; HER-2; ženské pohlaví; Breast Neoplasms; Receptor, ErbB-2; Trastuzumab; protinádorové látky imunologicky aktivní; Humans; radiation therapy; Female; trastuzumab; Antineoplastic Agents, Immunological; lidé; breast cancer